Social innovations to increase health coverage: evidence from a crowdsourcing contest in Ghana. Issue 6 (7th June 2022) - Dako-Gyeke, Phyllis; Asampong, Emmanuel; Opoku-Mensah, Kwabena; Tabong, Philip Teg-Nefaah; Awor, Phyllis; Tucker, Joseph D
Abstract : Objectives: Despite progress made to expand access to health service in Ghana, inequities still exist. Social innovations have been developed as community-engaged solutions to decrease inequities. Methods: In partnership with a multistakeholder group, our social innovation team organised a crowdsourcing contest to identify health innovations in Ghana. Informed by a WHO-Special Programme for Research and Training in Tropical Diseases framework, we organised a six-stage crowdsourcing challenge. Results: In all, 13 innovations were received in the contest, while 2 innovations were rejected after initial screening. The 11 innovations were reviewed by a panel of four independent expert judges. Inter-rated reliability index (kappa) was 0.86. Following the review of the average score, five top innovations were recognised. These submissions can be put into three main themes: technology and strengthening (eg, mHealth for cervical cancer screening, video directly observed therapy), inclusiveness and reaching the marginalised (people with disability and infertility) and data utilisation for project improvement (seasonal calendar to reduce morbidity and mortality of children under 5 for malaria, diarrhoea and pneumonia). Conclusion: In conclusion, this study shows that solutions to local problems exist. Therefore, policymakers, the government and development partners should support the scale-up of such innovations.